An outline of Christianity : the story of our civilization - Peake, A.S.; Parsons, R.G. (London : Waverly Book, 1926)
Contents: v.1. The birth of Christianity. - v.2. The builders of the church. - v.3. The rise of the modern churches. - v.4. Christianity and modern thought. - v.5. Christianity today and tomorrow.
Bibliography at end of each volume.
Keywords: Church history; Christianity